Fault Gouge Permeability Under Confined Conditions: An Investigation for CO2 Storage Applications - Aigerim Sekerbayeva; Ali Mortazavi; Randy D. Hazlett; Bahman Bohloli (Energies)
This investigation provides an in-depth experimental analysis of the prepared artificial fault gouge material on permeability characteristics as a function of the confining pressures and injection flow rate pertinent to both CO2 storage and subsurface fluid flow that addresses an ultimate challenge in CO2 storage. The purpose of the research is to gain a better understanding of the role of fault gouge material in structuring fluid flow patterns within geological media and improving the safety and efficiency of subsurface storage systems. In order to ensure the reproducibility of the experimental program, fault gouge material that resembled the size distribution and material type observed in the field and reported within the literature was purposefully designed and prepared. A set of core-flooding experiments were conducted to evaluate the relationships between permeability, confining pressure, and fluid flow rates. The subsequently obtained results showed that lower permeability is always the result of increasing confining pressure, highlighting the significance of fault gouge material for controlling fluid flow in fractured rock formations. These conclusions provide novel insights and can be applicable in practice when evaluating the integrity of CO2 storage sites, which calls for knowledge of permeability behavior under high-stress conditions.